A 'necessary evil' even during hard times? Public support for political parties in Portugal before and after the bailout (2008 and 2012). (November 2016) - Teixeira, Conceição Pequito; Tsatsanis, Emmanouil; Belchior, Ana Maria
Notwithstanding the prolific research on the crisis of democracy since the 1980s, the attention that has been given to political parties has not been enough to fully understand the (increasing lack of) citizen support for them. Additionally, there is too little research on how the economic context can contribute to changes in support for political parties. Focusing on the Portuguese case, this article has three main goals: to assess citizen support for parties before and after the economic crisis; to explore the contribution of the crisis to changes in the explanatory models of support; and finally, to identify the consequences of support for parties, with regard to electoral turnout. Findings reveal the economic crisis has affected support for parties in Portugal, specifically regarding diffuse-institutional support and party legitimacy. Changes in public support for parties between 2008 and 2012 have had consequences on voter turnout.